Pengaruh Kualitas Produk dan Citra Perusahaan terhadap Kepuasan Pelanggan Motor Matic Honda di Dealer Honda Anugerah Sejati Probolinggo (Studi Kasus pada Honda Beat) - I., Moh. Rosyiful Fikri; Tyas, Yayuk Indah W.; Junaidi, Junaidi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study focuses on examining the impact of product quality and corporate image on customer satisfaction, both individually and simultaneously at CV. Anugerah Sejati Probolinggo. The approach used in this research is quantitative descriptive, with data collection techniques through surveys and associative causal analysis. A total of 660 people were the population in this study, the sampling technique of which was using incidental sampling. Data using questionnaires with the data was analyzed through a series of tests, namely validity tests, reliability tests, classical assumptions, multiple linear tests, determination coefficient calculations, and hypothesis tests. This study shows that product quality and corporate image, when tested together or separately, have a significant influence on customer satisfaction levels at CV. Anugerah Sejati Probolinggo.